Studies on ferroelectric and nanomechanical response of single-layered PZT thick film for energy harvester applications. (26th October 2019) - Rath, Martando; Varadarajan, E.; Premkumar, S.; Shinde, Sd; Natarajan, V.; Ramachandra Rao, M. S.
Abstract: We have made an attempt to fabricate free standing warpage free PZT thick films of 100 µm thickness by tape casting method. The poly crystalline nature and nanoscale polarization switching of free standing thick film were confirmed using X-ray diffraction technique and piezo force microscopy, respectively. The piezoelectric coefficient ( d 33 ) of 100 µm free-standing Pb(Zr0.56 Ti0.44 )O3 [PZT] thick film was calculated using double beam laser interferometer and found to be 400 pm/V. From the results, it indicates that free-standing PZT thick films are suitable candidate for miniaturization of harvesting device by directly bonding them on microsystem components for microelectromechanical systems (MEMS) applications.